Financial Statement Fraud Before the Pandemic COVID-19 - Azizah, Widyaningsih (Manunggal Halim Jaya, 2024)
Financial statement fraud is a practice that can cause huge losses for investors, a lack of trust in the market and the existing accounting system, and the wrong decision-making process. Financial statement fraud can start from the manipulation of financial statements that are considered immaterial but then become a massive accounting scandal or start from the opportunistic behavior of managers so that their goals can be achieved. This study relies on the components of the fraud diamond to detect financial statement fraud, which consists of pressure, opportunity, rationalization, and ineffective monitoring. Pressure is proxied by external pressure, opportunity is proxied by ineffective monitoring, rationalization is proxied by auditor changes where auditor changes in companies can be seen as an attempt to eliminate fraud trials by previous auditors, and capability is proxied by changes in directors. This study succeeded in proving that pressure has a significant negative effect on financial statement fraud, and capability has no significant effect on financial statement fraud. Meanwhile, opportunity and rationalization do not affect financial statement fraud.